PEMANFAATAN MOBILE LEARNING UNTUK MENINGKATKAN KOLABORASI DALAM PEMBELAJARAN : SEBUAH KAJIAN LITERATUR - Setiono, Panut; Yuli Amaliyah; Erwin (UNIB Press, 2024)
This study looks at different mobile learning formats that can improve learning collaboration. The findings demonstrate that the use of mobile learning can greatly enhance students' favorable attitudes toward the subject, social skills, and cognitive abilities. Adaptive technology-enabled mobile learning fosters a more dynamic and inclusive learning environment by enabling students to participate in cooperative activities, share resources, and share ideas with their peers. Through repeated practice and peer evaluation, mobile learning has been demonstrated to boost student participation and accomplishment in the context of engineering and language education. This cooperative approach aids in the development of student competencies and permits flexibility in blended and distance learning models. In mobile learning, collaborative techniques help boost student enthusiasm, teacher-student connection, and pedagogical cooperation. As a result, mobile learning holds enormous promise to transform teaching methods, enhance the overall educational process, and close the achievement gap between students from diverse backgrounds. To optimize mobile-based collaborative learning, this article offers recommendations for educational institutions on how to incorporate suitable mobile technology, train teachers, and maintain fair accessibility.